(untitled) (Sains Humanika, 2022)
There are many studies that have proven that the use of Google Classroom in the teaching and learning process is seen to have a very effective impact on improving student achievement in academic achievement. However, the use of Google Classroom among primary school science teachers is still at a low level which may be due to teachers ’technological skills, usefulness and usability of Google Classroom, teachers’ attitudes and technological facilities in schools. Therefore, this study was conducted to examine the factors of Google Classroom use among primary school science teachers. There are five main factors that are given attention in this study, namely ICT skills factors, usability factors, ease-of-use factors, equipment factors and information technology facilities and attitude factors towards Google Classroom. This study was conducted using quantitative methods through a descriptive questionnaire on 81 teachers from primary schools in the district of Johor Bahru. Data were analyzed using Weka software with the decision tree method to see the factors of Google Classroom usage. The findings of this study indicate that the ICT skills factor is the dominant factor in determining the use of Google Classroom. TMK factors are also seen to affect several other factors such as attitude factors, usability factors and Google Classroom usability factors. For teachers with intermediate level ICT skills, the usefulness factor is a determining the use of Google Classroom. However, for teachers with a high level of ICT, all factors do not affect the use of Google Classroom. Therefore, it is hoped that teachers can equip themselves with knowledge related to ICT and knowledge related to applying the use of Google Classroom in science teaching and facilitation (PdPc).